2016
DOI: 10.18045/zbefri.2016.2.555
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability of recession in Croatia: Is economic sentiment the missing link?

Abstract: This paper aims to assess the possibility of predicting Croatian recessionary episodes using probit models. The authors first estimate a baseline static model using four leading indicators of recession (monetary base, unemployment, industrial production, and CROBEX stock market index). Lag lengths of up to 6 months are examined for each of the observed variables in the probit specification, and several important conclusions arise from the estimated models. First, the stock market and money supply exhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…market confidence) [23]. The results of many studies demonstrate that forecasting models can be expanded by economic sentiment indicators, with significant improvements in the performance of forecasting models [24,25]. This suggests that psychological factors govern the economic cycle to some extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…market confidence) [23]. The results of many studies demonstrate that forecasting models can be expanded by economic sentiment indicators, with significant improvements in the performance of forecasting models [24,25]. This suggests that psychological factors govern the economic cycle to some extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Obtained VAR results indicated that an increase in the stock exchange equity index increases Consumer confidence index whereby an increase in the Consumer confidence index has no effect on the stock exchange equity index. Erjavec, Sorić and Čižmešija (2016) assessed the possibility of predicting Croatian recessionary episodes using probit models which was augmented by the ESI variable (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). They came to conclusion that psychological factors largely govern the economic cycles in Croatia, growing in significance in times of economic hardship.…”
Section: Literature Reviewmentioning
confidence: 99%